Analysis of Cassava Noodle Business Development Strategy Using Porter's Five Force Approach in Serdang Bedagai Regency - Lestari Hulu, Rita Dwi; Daulay, Aqwa Naser; Atika, Atika (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
The development of micro, small and medium enterprises (MSMEs) in Indonesia shows a positive trend and has a significant contribution to the national economy. This study aims to analyze the development strategy of cassava sliced noodle business using porter's five force analysis. The research method used is qualitative descriptive with data collection techniques, namely observation, interviews and documentation. The informants in this study were five people, namely three sliced noodle entrepreneurs, one supplier of raw materials in the form of cassava, and one customer in Pegajahan Village, Pegajahan District, Serdang Regency. Meanwhile, the data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results of the study from the analysis of Porter's five forces show that the threat of entrants has high potential because of small capital, easy to imitate and raw materials that are easy to obtain, high buyer power because they already have buyer outlets or regular customers who buy, namely breakfast sales and also shops spread throughout Indonesia, high supplier power because they rely on only one supplier where the price is uncertain and also the quality of raw materials is uncertain, the threat of substitute products is high because it is easy to get substitute products, also products that are not widely known to the public and the threat of low competitor competition because their place does not need to market and only sells to one agent, as well as other competitors and there is no difference in the raw materials used, no advantages in the product and also relatively the same price. This study uses a qualitative method using observation techniques and also direct interviews with business owners as sources of information that are processed into data.